EFFECTIVENESS OF BIOFILTER MADE FROM PLASTIC WASTE TO DECREASE BOD, COD AND AMMONIA OF HOSPITAL WASTEWATER - Juniarta, Putu Sri; Budiarsa Suyasa, I Wayan; Sila Dharma, IGB (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 12 No 1 (2018), 2018)
This study aims to determine the influence of biofilter made from plastic waste to decrease  BOD, COD and Ammonia content and to determine the efficacy of its use to decrease BOD, COD and Ammonia content from the hospital’s wastewater. This study utilized aerobic biofilter processing through a batch system. Variables used in this research are wastewater processing through biofilter media made from plastic waste and processing without biofilter media, with 36 hours retention time. The parameters are BOD, COD and Ammonia content. From the statistical analysis, the use of biofilter media made from plastic waste gives a significant effect to decrease  BOD and Ammonia content but made no significant effect to decrease COD. Plastic waste biofilter processing system is very effective to decrease BOD (84,85%), less effective to decrease COD (31,73%) but effective enough to decrease ammonia (50,60%), meanwhile, the standard quality of plastic waste biofilter processing system is effective to reduce BOD and COD content but not effective to reduce the ammonia content  after 36 hours of processing time. Further research is needed to study the efficacy of biofilter media made from other type of plastic waste. Moreover, a combination of anaerob-aerobic biofilter processing is required to improve processing efficacy.   Keywords : biofilter; plastic waste; hospital wastewater; BOD; COD;  ammonia